Tracing the Provenance of the Devonian Limestone of Telen River, East Kalimantan - Herman Darman (Berita Sedimentologi, 2021)
H. Witkamp found an outcrop with Devonian Limestone in East Kalimantan in 1925. In 1989, an expedition run by Institute of Technology Bandung (ITB) reinvestigated the outcrop and concluded that the Devonian Limestones in Telen River were boulders within a Permian formation. This paper gives a wider overview on the distribution of Devonian rocks in Asia Pacific region and discusses their possible origin.Based on the distribution map of Devonian rocks in the region, the Devonian limestone in Borneo is very isolated. The closest Devonian limestones are about more than 2000 km away. Probably the Devonian limestone in Telen River has been separated away from its origin by significant tectonic movement. There are several theories and models related to the formation history of this area, which makes it very complex. To understand the origin of these limestones, the geology needs to be restored to their time and place of deposition of the Devonian limestone.